A Dual-Phase Approach to Reveal the Presence and Impact of the TLL Transition in Polymer Melts. Part II. The Theoretical and Practical Relevance of the TLL Existence and Characteristics on the Understanding of the Melt Thermal Analysis and Rheological Properties of Polymers: Duality and Cross-Duality of the Interactions. Issue 10 (8th April 2021) - Ibar, Jean Pierre
Abstract: In Part I of these 2 parts article, we derived mathematically the existence of a unique state for polymeric melts, occurring at a specific temperature above Tg, which we recognized to be the liquid–liquid transition, TLL, observed and described by Boyer and others. TLL is the temperature at which the melt is in an iso-free-volume and iso-enthalpic state independent of the molecular weight. It is a fundamental property of the material. The purpose of part II is to examine and explain the following: 1) the elusive character of TLL (at the origin of the controversy about the existence of TLL in the past), 2) the increase of free volume at TLL, and 3) the endothermal change of heat capacity on heating across TLL . Finally, our objective is to provide an explanation of TLL and emphasize its importance as an example of a self-dissipative dynamic process that converts, at TLL, into a classical thermally activated process. In this article, the experimental evidence found in the literature for TLL is critically examined to point out the often biased reviews offered by the antagonistic authors of a controversy, here the pros and cons TLL . We propose a Dual-Phase origin of the interactions in polymers to explain the weak and elusive manifestations of TLL and show, by DSC, that the TLL manifestations are made much more visible and prominent when the samples' state has been brought out of equilibrium. We analyze, in detail, the thermally activated depolarization of samples which have been submitted to a polarization stage by a voltage field. The experimental technique of thermal stimulated depolarization (TSD), and its sister derivative the thermal windowing deconvolution (TWD), are unique and powerful analytical tools that can experimentally characterize "interactive coupling", the factor that we have assumed is quantitatively responsible for the behavior of polymers and in particular of TLL . The existence and the characteristics of TLL were understood and predicted in Part I from rheological results by the use of the Thermo–Vogel–Fulcher equation whose thermo-kinetic terms, ΔH, ΔS, and T∞, could be interpreted by the interactive coupling of the local free volume and the rotational isomeric conformational state of dual-conformers belonging to the macromolecules, themselves embedded in a collective dissipative system of interactions. The statistics controlling the interactive coupling parameters was described by the Dual-Phase and Cross-Dual-Phase models. In Part II, the same models are used to explain the interactive coupling manifestations specific to the TSD and TWD results. We show that certain characteristics of the TSD and TWD results are directly related to specific parameters of the Dual-Phase model. It is the case for the transitions visible by TSD, such as Tg, ρ related to space charges and local free volume (F-conformers), and TLL marking the end of the specific impact of the Dual-Phase statistics on the properties. It is also the case when interactive coupling is analyzed by TWD: the compensation of the enthalpy and entropy of activation of the relaxations taking place at various polarization temperatures only occurs below TLL, permitting its specific determination. We conclude pointing out the perhaps crucial importance of TLL in establishing the distinct role of thermal energy in structuring or modulating the dynamics of the interactions. The Dual-Phase view of the interactions in polymers suggests that the local density difference between the b-grains and the F-conformers is "time-averaged" by the constant wiping (above Tg ) of an "elastic dissipative wave" having a frequency, ωo, i.e., a function of temperature and molecular weight, and thus is different from the Brownian dissipation, i.e., the thermal fluctuation characteristic of the Boltzmann's mean field (the classical kT/h term). The elastic dissipative wave kinetically loses its collective modulation role and becomes the thermal wave at TLL .